Meningkatkan Ketrampilan Sosial Melalui Metode Bermain Peran Pada Siswa UPT SD X - Cica Mustika; Prianggi Amelasasih (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2024)
This research aims to improve the social skills of fourth grade elementary school students by using the role playing method. The main subject, a female student who tends to be quiet and lacks interaction in class, experiences obstacles in aspects of social skills, such as communication, cooperation, sharing, participation and adaptation. The role playing method was applied in three meetings involving three classmates as supporters. The results of the intervention show a significant improvement in students' social skills, although there are still several things that need to be improved. Role playing techniques have proven to be effective in helping students develop the courage to interact and participate actively in the school environment. It is hoped that this method can be a reference for teachers and parents to help children develop social skills on an ongoing basis.